Multimaterial Mesh-Based Surface Tracking - Da, Fang; Batty, Christopher; Grinspun, Eitan (Association for Computing Machinery, 2014)
We present a triangle mesh-based technique for tracking the evolution of three-dimensional multimaterial interfaces undergoing complex deformations. It is the first non-manifold triangle mesh tracking method to simultaneously maintain intersection-free meshes and support the proposed broad set of multimaterial remeshing and topological operations. We represent the interface as a non-manifold triangle mesh with material labels assigned to each half-face to distinguish volumetric regions. Starting from proposed application-dependent vertex velocities, we deform the mesh, seeking a non-intersecting, watertight solution. This goal necessitates development of various collision-safe, label-aware non-manifold mesh operations: multimaterial mesh improvement; T1 and T2 processes, topological transitions arising in foam dynamics and multiphase flows; and multimaterial merging, in which a new interface is created between colliding materials. We demonstrate the robustness and effectiveness of our approach on a range of scenarios including geometric flows and multiphase fluid animation.
© ACM, 2014. This is the author's version of the work. It is posted here by permission of ACM for your personal use. Not for redistribution. The definitive version was published in Da, F., Batty, C., & Grinspun, E. (2014). Multimaterial Mesh-Based Surface Tracking. Acm Transactions on Graphics, 33(4), 112. https://doi.org/10.1145/2601097.2601146
Keywords: 3-Dimensional Grain-Growth; 3 Dimensions; Collisions; Dynamics; Evolution; Fluid Simulation; Front-Tracking; Interface Tracking; Multimaterial Flows; Nonmanifold Meshes; Robust Treatment; Surface Tracking; Topology; Topology Change